LC–MS/MS quantification of next-generation biotherapeutics: a case study for an IgE binding Nanobody in cynomolgus monkey plasma. (May 2014) - Sandra, Koen; Mortier, Kjell; Jorge, Lucie; Perez, Luis C; Sandra, Pat; Priem, Sofie; Poelmans, Sofie; Bouche, Marie-Paule
Background: Nanobodies ® are therapeutic proteins derived from the smallest functional fragments of heavy chain-only antibodies. The development and validation of an LC–MS/MS-based method for the quantification of an IgE binding Nanobody in cynomolgus monkey plasma is presented.Results: Nanobody quantification was performed making use of a proteotypic tryptic peptide chromatographically enriched prior to LC–MS/MS analysis. The validated LLOQ at 36 ng/ml was measured with an intra- and inter-assay precision and accuracy <20%. The required sensitivity could be obtained based on the selectivity of 2D LC combined with MS/MS. No analyte specific tools for affinity purification were used. Plasma samples originating from a PK/PD study were analyzed and compared with the results obtained with a traditional ligand-binding assay. Excellent correlations between the two techniques were obtained, and similar PK parameters were estimated.Conclusion: A 2D LC–MS/MS method was successfully developed and validated for the quantification of a next generation biotherapeutic.